Shariah Models-Based on Ethics Innovation In Nursing Documentation - Halimatussakdiah Halimatussakdiah; Hidayat Arifin; Wiwin Haryati; Alhuda Alhuda; Nur Asiah (Journal of Global Pharma Technology, 2020)
Introduction: Nurses who work full time require religious support in patient care and professional documentation tools. The purpose of this research was to test a model development of patients’ satisfaction through nurse performance with an empirical study on innovation in nursing services and shariah ethics. Methods: A quantitative design was used with a cross-sectional approach. The samples were 420 postoperative patients. Respondents were obtained through multistage sampling. The independent variables were innovation service with Electronic Nursing Documentation and shariah-based ethics. Nurse performance was the mediating variable and the dependent variable was patient satisfaction. Data collection was performed using a questionnaire and data analysis with SEM version 22. Results: The results of this study indicated there was use of standard operating procedures in patient care about shariah-based ethics, which can improve the quality of nursing services where nurses can document the patient's nursing process comprehensively using Electronic Nursing Documentation (END). All the variables tested in the model development, namely service innovation, shariah ethics, and nurse performance, affects patient satisfaction. SEM test results obtained GFI (Goodness of Fit Index) values which should be within the expected cut-off value range (p Value ≤ 0.05). Conclusion: The use of SOPs on shariah ethics with END is interrelated between service innovation, shariah ethics and nurse performance and affects patient satisfaction. It is expected that nurses will be able to provide shariah ethics-based services and documentation to improve patient satisfaction.